Study of Cytotoxic Effect of Aqueous Extract Fenugreek(Trigonella Foenum Graecum L.S) Seeds and The New Complexes of Rh (?) and Pd (?) on Cancer Cell Lines (Baghdad Science Journal, 2018)
The effect of the aqueous extract of fenugreek seeds (Trigonella Foenum Graecum L.), Rhodium complex (?) with formula [RhL2CLH2O].1 1/2 ETOH and palladium (?) [pdl2].2ETOH,where L=2-hydroxy phenyl piperonalidine was studied on two cancer cell lines. The first cell line was intestine cancer of female albino mice (L20B), the second one was Rhabdomysarcomas (RD)cell line in human. The activity of the new complexes and the aqueous extract was compared to the well-known anticancer drug (cis-platin) by utilizing the in vitro system. The cell lines were treated with four concentrations of cis-platin 31.25,62.5,125 and 250 ?g/ml for 72 hour exposure time. The same concentrations were used with extract and the new complexes. This study showed that the aqueous extract, Rhodium (?) and palladium (?) complexes have a promising anticancer cell activity as noticed from their effect on inhibition of the cancer cells . Inhibition rate was increased with concentration for the three treatments and it was found to be significant differences (p